Indirect lightning surge analysis of insulated rail bracket and station arrester in a fourth rail LRT system - Abd Rahman, Farah Asyikin; Ungku Amirulddin, Ungku Anisa; Ab Kadir, Mohd Zainal Abidin; Osman, Miszaina (IEEE, 2023)
This paper presents a study comparing the performance of a fourth rail direct current (DC) urban transit system when affected by an indirect lightning strike. Two different designs were used: one with a Cast Epoxy (CE) bracket equipped with a 3EB4-010 arrester, and the other with a Glass Reinforced Plastic (GRP) bracket equipped with a PDTA09 arrester. To replicate the indirect lightning strike, a lightning induced overvoltage was generated using the Rusck model. The model utilized the sum of two Heidler functions as the input for the lightning channel base current, assuming a perfectly conducting ground. The objective of this study is to determine whether an indirect lightning strike has any impact on the performance of the insulated rail bracket and station arrester of the LRT Kelana Jaya line, considering their different materials and residual voltage limits, respectively. Simulations were conducted using the Electromagnetic Transients Program - Restructured Version (EMTP-RV), and the performance of the two designs was compared when subjected to a 30 kA (5/80μs) induced current. The results showed that the GRP bracket, which has a higher permittivity, performed better when paired with the PDTA09 arrester, which has a lower residual voltage limit. This combination resulted in slightly lower induced overvoltage and significantly lower residual voltage being clamped by the station arrester.